Individual Sanctions of Competition Law: A Comparison between the UK and Turkey. (4th November 2019) - Caliskan, Samet; Oner, Saliha
Abstract : It is a highly advocated view that a competition law with sanctions targeting individuals would achieve a greater deterrent impact than one that does not. Having introduced individual sanctions does not, however, guarantee that a market would have less anticompetitive conduct, because these sanctions are effective only insofar as they are severely implemented on wrongdoing individuals. UK competition law is one example of this issue because cases where individuals have been targeted and punished are significantly fewer than the authorities expected, in spite of it being more than 15 years since individual sanctions were introduced amidst high expectations. This article examines the individual sanctions of competition law in the UK and Turkey. It argues that Turkey is on the right path by departing from the way in which EU law enforces the rules of competition law, and is moving closer to UK law. However, it is argued that further steps should be cautiously considered to avoid the same issues which UK competition law is currently experiencing, as there are serious doubts that the latter has achieved the desired deterrent effect.